Trade associations in Malaysia - Ismail, Shamsudin; Minai , Badriyah; Loo, Sin Chun; Han, Chun Kwong (1987)
Trade associations play an important role in the business environment of Malaysia. A study was conducted in 1986 to examine several aspects of trade associations such as corporate objectives, membership, organizations, administration and resource utilization.